2004
DOI: 10.1136/gut.2003.035568
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of serotonin: what a clinician should know

Abstract: SUMMARYThe pharmacology of serotonin (5-hydroxytryptamine or 5-HT) in the gut has been the centre of intense interest and research for several decades. Although it is now recognised that 5-HT is contained in intrinsic enteric neurones (where it works as a neurotransmitter), enterochromaffin cells of the mucosa are the main source (more than 90%) of the body's 5-HT. In the gut, 5-HT is an important mucosal signalling molecule targeting enterocytes, smooth muscle cells, and enteric neurones. Application of exoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
110
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 178 publications
2
110
1
3
Order By: Relevance
“…Interestingly, the IBS-C patients in this population were the most responsive to vitamin D supplementation in terms of a striking improvement across nearly all IBS symptoms. 47 Because IBS-C patients are thought to possess lower gut serotonin levels, 48 the responsiveness of these patients to vitamin D supplementation is consistent with the actions of vitamin D to raise gut TPH1/serotonin levels 25 and with our current hypothesis that vitamin D, via induction of the intestinal TPH1 gene, may play a role in IBS pathophysiology. While this study was limited by its small sample size, our IBS cohort displayed a trend toward diminished serum vitamin D levels relative to our non-IBS control group.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, the IBS-C patients in this population were the most responsive to vitamin D supplementation in terms of a striking improvement across nearly all IBS symptoms. 47 Because IBS-C patients are thought to possess lower gut serotonin levels, 48 the responsiveness of these patients to vitamin D supplementation is consistent with the actions of vitamin D to raise gut TPH1/serotonin levels 25 and with our current hypothesis that vitamin D, via induction of the intestinal TPH1 gene, may play a role in IBS pathophysiology. While this study was limited by its small sample size, our IBS cohort displayed a trend toward diminished serum vitamin D levels relative to our non-IBS control group.…”
Section: Discussionmentioning
confidence: 62%
“…Fatores culturais e decorrentes de hábitos alimentares têm sido isolados com sugestões de agentes etiológicos. 25,26 Hiperalgesia visceral, estresse, abuso físico e sexual têm sido elementos associados como participantes do conjunto de dados clínicos, englobado no universo dessa moléstia [1][2][3][4][5][6][7][8][9] , da mesma forma ocorrendo com as enterites bacterianas e virais, sem que, no entanto, seja possível destacar um elemento marcador. 27,28 São tantas as teorias e complexas as investigações e conclusões que a SCI passa a ser vista sob um conjunto heterogêneo de desordens com sintomas parecidos, mas de diferentes etiologias [29][30][31][32] que retroalimentam mais especulações sobre uma causa básica, o que, sem dúvida alguma, favorece a " medicalização" e a emergência de procedimentos subsidiados pela medicina alternativa 33 .…”
Section: Discussionunclassified
“…Apesar de ser comum, com incidência populacional de até 30% (predominando nas mulheres), e de ser alvo de estudos com destaque para diversos hormônios de ação gastrintestinal [3][4][5][6][7][8][9][10][11] , o diagnóstico e o tratamento dessa doença nem sempre são tarefas fáceis de serem executadas, sobretudo pela falta de um marcador que defina sua natureza, não só para retirá-la da classe de " doença de diagnóstico de exceção", como para permitir opções terapêuticas efetivas. 12,13 Baseados na observação de que a Síndrome do ceco móvel (SCM) engloba sintomas que se superpõem aos da SCI 14 nossos objetivos, ao desenvolver um estudo prospectivo não casualizado, foram: a. demonstrar a relação de causa e efeito entre o ceco móvel e a SCI, b. avaliar o resultado da cecopexia, como método de tratamento de pacientes com Síndrome do cólon irritável (SCI) ou com desconforto abdominal de etiologia desconhecida; e c. mostrar que o ceco móvel pode ser considerado como o primeiro marcador anatômico para a SCI.…”
unclassified
“…It has been demonstrated that 5-HT 4 -receptor activation may be associated with esophageal peristalsis and LES tone. 9,12) Of the 5-HT receptor antagonists tested, contraction by 5-HT was significantly reduced by adding the 5-HT 4 receptor antagonist, but not by the 5-HT 3 receptor antagonist. Although, the 5-HT 2B receptor antagonist SB204741 and 5-HT 2C receptor antagonist SB242084 partly attenuated 5-HTinduced contraction in LES strips, LES contraction was not induced by the 5-HT 2A receptor agonist 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (data not shown in Figs.…”
Section: Discussionmentioning
confidence: 99%